Diversity of plant-parasitic nematodes on medicinal plants in melinh station for biodiversity, Vinh Phuc Province, Vietnam - Tien, Nguyen Huu; Duyen, Nguyen Thi; Huy, Le Duc; Neriza, Nobleza; Phap, Trinh Quang (Academia Journal of Biology, 2019)
Plant-parasitic nematodes are known as one of the most important pests attacking various plants in the world, and investigating the nematode component is very essential for management of this pest and prevent damage to plants in general. Our survey of plant-parasitic nematodes on medicinal plants in Melinh Station for Biodiversity, a place for conservation of precious plants and animals in Vietnam, identified ten species that belong to nine genera, five families, and two orders of plant-parasitic nematodes parasitizing six medicinal plants. Excoecaria cochinchinensis was parasitized by the highest number of nematode genera (5 genera, including Xiphinema, Discocriconemella, Meloidogyne, Helicotylenchus, and Hemicriconemoides), while Hymenocallis littoralis was associated with the highest number of plant-parasitic nematodes (2060 nematodes/250g soil). The results also showed that Discocriconemella limitanea was found to be a dominant species with the highest number of individuals on 6 medicinal plants, and the genus Helicotylenchus had the highest frequency of appearance (5/6 plants or 83.3%). These nematodes caused symptoms such as yellowing leaves, root galls, and root lesions, which directly affect the quality and yield of medicinal plants. Based on the results, this study showed that plant-parasitic nematodes are a potential threat to the cultivation of medicinal plants in Melinh Station for Biodiversity, and thus, control measures should be applied to ensure sustainable cultivation of medicinal plants in this place.